Design and Build an Automatic Feeding System for Catfish Farming based-on Internet of Things (IoT) - Fajri, Mukhlis Surito; Asrizal, Asrizal; Amir, Harman; Mairizwan, Mairizwan (Department of Physics, Universitas Negeri Padang, 2024)
Fish farming represents a sector aimed at boosting the national economy. The Ministry of Marine Affairs and Fisheries has prioritized programs to support the growth of catfish farming.. However, there are still obstacles experienced by cultivators such as irregularities in feeding time and uneven distribution of feed. Therefore, a solution is needed in the form of designing an efficient system in providing fish feed. The system is developed using ESP32 microcontroller, servo motor, stepper motor, loadcell, and connected to the website for remote control. The system utilizes a motor, load cell, and is integrated with a website for remote operation. This research employs an engineering approach, focusing on system design and testing. The findings indicate that the system achieves an average feed weight measurement accuracy of 98.31%, demonstrating reliable performance in both laboratory and field-scale tests. This system is expected to increase efficiency, practicality, and effectiveness in catfish farming, as well as providing real-time information about feed and feeding schedules.